Current practices of psychoeducation interventions with persons with bipolar disorders: a literature review - Levrat, Vanessa; Favre, Sophie; Richard-Lepouriel, Hélène (Frontiers in Psychiatry, 2024)
This review sought to summarize the literature on current practices and forms of psychoeducation in the management of patients with bipolar disorder, including only randomized controlled trials to ensure the best level of evidence. An extensive review of the available literature was conducted using PubMed/MEDLINE, Embase, and PsychInfo databases from inception to April 28th, 2022. The search yielded 381 studies. Seventy articles were included after removing duplicates and applying the inclusion/exclusion criteria. A best-evidence synthesis was used to identify the key results of each study and summarize the outcomes. Eleven descriptive categories were made. They encompass different forms of psychoeducation compared or combined with other psychosocial interventions, varying in setting (individual or group), with or without family members, structured or unstructured, mediated or not by digital tools (smartphone, internet). Globally, these studies show that psychoeducation is important in the treatment of bipolar disorder, as it leads to a decrease in relapses, mood episodes, hospitalizations, and improved functioning or quality of life. Some studies also showed the benefits of psychoeducation on the patient's level of knowledge of pharmacological treatment and the disorder or compliance with medication, as well as reduced self-stigma. The limitations of this review are linked to the selection of only RCTs and the reliance on their post-hoc analyses. This review confirms the benefit of psychoeducation and psychosocial interventions on the evolution of bipolar disorder (in different outcomes, including quality of life, relapse, and rehospitalization rates, for example). More recent interventions, such as mindfulness or online psychoeducation, represent an interesting option but more evidence is needed.